A framework analysis of free-text data from the neonatal survey 2014. Issue 3 (June 2018) - Ainley, Esther; King, Jenny; Käsbauer, Susanne; Cooper, Robyn
Abstract: Objective: To systematically analyse parents' free-text comments provided in a survey about their experiences of neonatal care. Methods: Using framework analysis of free-text data from the survey, a thematic framework was developed for coding 3738 comments. Most themes had positive and negative subcategories. Comments within the most frequently coded themes were re-coded into sub-themes to provide a more detailed insight into parents' experiences. Results: Three quarters of comments referred to the 'care from staff' (n = 2447) with the majority (81%) being positive. Of these comments, a large proportion were 'general' or about positive 'staff behaviour/attitude'. The most frequently coded comments on parents' negative experiences focused on relationships formed with staff, specifically, information and communication (n = 734). Conclusions: Neonatal units wishing to understand how best to improve parents' experiences would benefit from including an open-ended question in surveys of parents and reviewing these alongside the quantitative data.